Microbicides and the environmental control of nosocomial viral infections() - Sattar, S.A (J Hosp Infect, 2004)
Viruses are important causes of acute and chronic diseases in humans. Newer viruses are still being discovered and those that are already known are being incriminated in the aetiology of clinical conditions with hitherto unknown causes. Apart from frequently causing infections in the general community, many types of viruses are also significant nosocomial pathogens. While it is generally agreed that we underestimate the proportion of nosocomial infections that are viral, due to a lack of routine monitoring, viruses easily account for more than 30% of the cases of hospital-acquired infections in many paediatric settings. Indeed, the relative importance of viruses in this respect is increasing due to a number of societal and demographic changes as well as alterations in healthcare practices. Safe vaccines against many common nosocomial viral agents are currently unavailable while there is also a virtual lack of effective and affordable chemotherapy against them. There is, therefore, renewed emphasis on preventive strategies by better understanding of the relative importance of various vehicles in the nosocomial spread of viruses and by infection control using microbicides. This, in turn, has stimulated considerable interest in the development of formulations that are not only safer but which also have demonstrated activity against major types of nosocomial viral pathogens. Further, much work is now underway to design better methods to assess the virucidal activity of microbicides used to decontaminate hands, reusable medical devices and environmental surfaces in critical areas of healthcare settings. It is anticipated that these approaches will result in reducing the health and economic impact of nosocomial infections due to viruses.